Analisis Materi Ekosistem dalam Buku Teks SD Kelas V: Studi Dokumentasi Kualitatif Deskriptif - Wulan Fatya Revyani (GENFABET: Generasi Pendidikan Dasar, 2025)
This study undertakes a comparative analysis of two Science (Ilmu Pengetahuan Alam – IPA) textbooks concerning ecosystem material for fifth-grade elementary school students. Each textbook distinctively represents the 2013 Curriculum (Student Book Theme 5 Ecosystem) and the Merdeka Curriculum (IPAS-BS-KLS-V Book), respectively. Employing a descriptive qualitative methodology, the research utilized a documentary study approach. A document analysis sheet served as the primary research instrument, facilitating the identification and comparison of the material's scope, pedagogical approaches, and core emphases presented in both textbooks. The analysis reveals that while both resources offer a comprehensive treatment of ecosystem concepts, fundamental distinctions exist in their structural organization and primary focus. The 2013 Curriculum textbook adopts an integrated thematic approach, interweaving ecosystem topics with various other subjects to foster a holistic learning experience, simultaneously stressing character development and literacy skills. In contrast, the Merdeka Curriculum textbook centers on inquiry and project-based learning, thereby prioritizing in-depth conceptual understanding and the cultivation of science process skills through active exploration. The implications of these findings underscore the critical importance for educators to comprehend the unique characteristics and curricular emphases of each textbook when selecting or combining learning resources. This understanding is vital for optimizing the attainment of learning objectives and effectively accommodating diverse student learning styles.